Food acquisition, preparation, and consumption practices in South Asia: A scoping review of assessment tools - Patwardhan, Sharvari; Boncyk, Morgan; Avula, Rasmi; Blake, Christine E.; Akter, Fahmida; Das, Jai K.; Silva, Renuka; Menon, Purnima; Scott, Samuel P. (Elsevier, 2025)
Assessing behaviors related to food choice at individual- and household-levels is essential for improving household diets, but assessment tools are limited. We conducted a scoping review to identify gaps in existing assessment tools for food acquisition, preparation, and household consumption practices in South Asia, where diets are rapidly changing. We undertook systematic keyword searches of three databases (PubMed, Scopus, and Web of Science Core Collection) to identify studies assessing food acquisition, food preparation, and household consumption practices in Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka, published in English between 2000 and April 2025. Two reviewers independently screened titles, abstracts, and full texts, and extracted data on study characteristics and the assessment tools used to examine the food choice behaviors. Of 13,160 unique articles identified, 50 were included for synthesis. Food acquisition behaviors (e.g., what and how often food is purchased, changes in food purchases) were assessed by 26 studies, food preparation (e.g., cooking habits, intra-household distribution of responsibilities, preparation methods) by nine studies, and household consumption practices (e.g., timing, snacking, meal skipping, eating away from the home) by 30 studies. Most studies used quantitative methods (n=34), some used qualitative methods (n=13), and few used mixed methods (n=3). Likert scales and semi-structured interviews were the most used tools for quantitative and qualitative assessments, respectively. Across the 50 studies, 40 different tools were used to assess food-related behaviors and only 14 studies claimed using validated tools. Few studies included a full tool in text or in supplemental material (n=23). Currently, there is little alignment on how to assess food choice behaviors in South Asia, highlighting the need for a contextually adaptable repository of tools. Adapting and validating existing tools, rather than creating new ones, could improve efficiency, continuity, and comparability.